Strategi Bersaing antara Produk Susu Ultramilk dan Cimory Menggunakan Teknik Analisis Game Theory dan Marcov Chain - AZ Zahra, Nabila Khairunnisa; Darayani, Nur Shabrina; Yuliani, Novita (Fakultas Teknik Universitas Tulang Bawang, 2024)
The competition in the Ultramilk milk market is becoming increasingly fierce due to strong competition from various competitors in the dairy processing industry, including brands like Cimory that are becoming more popular among consumers. This research aims to understand how brand switching occurs among Cimory and Ultramilk packaged milk consumers and to identify effective marketing strategies to retain customers. The methods used in processing the research data involve Markov Chain and Game Theory. The research was conducted by distributing questionnaires to Industrial Engineering students of the 2020 class at Singaperbangsa Karawang University. The results of the study indicate that the factors influencing brand switching are the size of the milk packaging. Marketing strategies that need to be improved for both milk products include pricing, flavor variations, packaging, and product availability. From the results of the Markov chain calculations on Ultramilk and Cimory milk, the researchers concluded that the market share forecast for the next 5 years shows an increase in Cimory milk sales by 18% and a decrease in Ultramilk sales by 4%, with variable chances of change each year. Keywords: Game Theory, Markov Chain, Marketing Strategy, Packaging Milk.